A multi-criteria optimization study for locating industrial warehouses with the integration of BIM and GIS data. (2nd November 2021) - Asgari Siahboomy, Mehdi; Sarvari, Hadi; Chan, Daniel W.M.; Nassereddine, Hala; Chen, Zhen
ABSTRACT: One of the newest advancements in manufacturing and project management is Building Information Modeling (BIM) which uses creative processes for production, analysis, and management of building information. On the other hand, the output of the Geographic Information System (GIS) model includes one or more actual locations, which satisfy all needs. It provides points related to the BIM tool and it creates a 3D model for visualizing the optimum location. Integration of GIS and BIM can bring about several advantages including optimum locating. The aim of the current study is to propose a useful model for locating warehouses in large manufacturing factories using a BIM-GIS integrated model. To this end, BIM was used for simulation and locating of product warehouses in the casting unit of Esfahan's Mobarakeh Steel Company (EMSC) in Iran. In order to meet these aims, several locations were selected in the EMSC compound, and decision making regarding three superior alternatives which were carried out by creating a 3D model of the warehouse and fitting of the model in three suggested locations. Using the extant literature, interviews with experts and managers, and survey questionnaires, essential criteria affecting the optimum locating of industrial warehouses were extracted based on the Building information modeling data. Then, the Analytic Hierarchy Process (AHP) method was used for data analysis. The results indicated that among various criteria, economic–social and crisis management criteria had the highest weights. These results were then used for selecting the optimum locating for the construction of warehouses.